External Marketing and its Importance in Developing International Economic Relations for Oil-Exporting Countries - Omaran Aun Allah Milad (Journal of Scientific and Human Dimensions, 2026)
This research paper investigates the pivotal role of external marketing strategies in bolstering the international economic relations of oil-exporting countries. While these nations have historically relied on the inherent value of crude oil, the shifting global energy landscape characterized by the rise of renewables and fluctuating market demands necessitates a robust marketing approach to maintain competitive advantages and foster strategic partnerships. The study explores how external marketing, beyond mere promotion, functions as a multidimensional tool encompassing diplomatic economic branding, market diversification, and the strengthening of bilateral trade agreements. By analyzing the intersection of marketing principles and international political economy, the research identifies how oil-exporting states can leverage their primary resource to catalyze non-oil sector growth and enhance their global economic footprint. The methodology employs a descriptive-analytical approach, utilizing case studies from major oil producers to evaluate the effectiveness of current marketing frameworks. Preliminary findings suggest that countries adopting sophisticated external marketing models experience more resilient economic ties and greater stability in foreign direct investment (FDI) inflows. The paper concludes with strategic recommendations for policymakers to integrate marketing intelligence into their national economic visions, ensuring long-term sustainability in an increasingly volatile global market